2018
DOI: 10.1371/journal.pone.0201160
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopeptide COR-1 to treat beta1-adrenergic receptor antibody-induced heart failure

Abstract: RationaleDespite advances in pharmacotherapy, heart failure still incurs significant morbidity and mortality. Stimulating antibodies directed against the secondextracellular loop of the human ß1-adrenergic receptor (anti-ß1EC2) cause myocyte damage and heart failure in rats. This receptor domain is 100% homologous between rats and humans.Objectiveß1EC2-mimicking cyclopeptides (25-meric) markedly improved the development and/or course of anti-ß1EC2-mediated cardiomyopathy. Further developments should be investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…For the development of β-MoDE-A we utilized an existing, high affinity cyclic peptide ligand of anti-β1AR antibodies called COR1. 18 COR1 constitutes a molecular mimic of the second extracellular loop of the β1AR, and contains the entirety of the recognition epitope of agonistic anti-β1AR antibodies. Thus, β-MoDE-A 1 was synthesized from an azide-labeled COR1 peptide and a tri-GalNAc ASGPR ligand bearing a strained dibenzylcyclooctyne via strain-promoted azide-alkyne cycloaddition (see Supporting Information for synthetic details and characterization data).…”
Section: Synthesis and Characterization Of β-Mode-amentioning
confidence: 99%
See 2 more Smart Citations
“…For the development of β-MoDE-A we utilized an existing, high affinity cyclic peptide ligand of anti-β1AR antibodies called COR1. 18 COR1 constitutes a molecular mimic of the second extracellular loop of the β1AR, and contains the entirety of the recognition epitope of agonistic anti-β1AR antibodies. Thus, β-MoDE-A 1 was synthesized from an azide-labeled COR1 peptide and a tri-GalNAc ASGPR ligand bearing a strained dibenzylcyclooctyne via strain-promoted azide-alkyne cycloaddition (see Supporting Information for synthetic details and characterization data).…”
Section: Synthesis and Characterization Of β-Mode-amentioning
confidence: 99%
“…6 These antibodies are believed to drive disease by chronically stimulating β1AR, 9-11 and the presence of antibody worsens mortality rates by up to threefold in certain patient subsets. [12][13][14][15][16] Recent animal studies have demonstrated that these anti-β1AR antibodies are sufficient to induce HF, 17,18 and neutralization of anti-β1AR antibodies using peptide mimics of β1AR can reverse HF in rats. 18 Furthermore, removal of these autoantibodies from HF patients through IA improves heart function and survival rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Consequently, B cells and autoantibodies are emerging targets in CHF therapy. [6][7][8][9][10] Among various heart-reactive autoantibodies discussed in the above context, autoantibodies against cardiac G-protein-coupled receptors (GPCRs) are candidates that have been studied earlier. 2,11,12 CHF-associated GPCR autoantibodies are intriguing candidates because they impact receptor-mediated autonomous heart regulation and thereby damage the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Heart‐reactive autoantibodies potentially contribute to cardio‐pathogenesis because CHF‐like symptoms can be transferred from patients to mice via B lymphocytes 5 . Consequently, B cells and autoantibodies are emerging targets in CHF therapy 6–10 …”
Section: Introductionmentioning
confidence: 99%